(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2005)
This study is an offering in the growing generative collaboration between ecopsychology and phenomenology. Viewing our ecological peril as a crisis of consciousness and culture, ecopsychology works for a radical transformation of humankind’s dissociative relationship with the other than human natural world. This article considers ecopsychology’s critique of the modernist enterprise of gaining (supposed) security and power through technological domination of nature and economic expansion. Ecopsychology fosters movement beyond our exclusionary identification as ego-centered subjects; our belief in a real and inevitable dualistic separation of humans and nature; and our anthropocentric view of humans as the exclusive locus of meaning and value. Showing that these concerns are central for Heidegger and Merleau-Ponty, this study explores how the phenomenological tradition and ecopsychology can be powerful allies.